Faktor-Faktor yang Berhubungan dengan Penyembuhan Ulkus Diabetik pada Pasien Diabetes Melitus Tipe 2 di RSUD Toto Kabila - Suleman, Sitti Nadia; Mahmud, Zulkarnain (Jurnal Ilmu Kesehatan dan Gizi, 2026)
This study aimed to identify and analyze factors related to the healing of diabetic ulcers among patients diagnosed with Type 2 Diabetes Mellitus at Toto Kabila Regional Hospital. An analytical observational study with a cross-sectional design was conducted. The study included all eligible patients through a total sampling technique, resulting in 22 respondents. Data were collected to assess the association between age, duration of diabetes, dietary adherence, and diabetic ulcer healing. Statistical analysis was performed using the Chi-square test, with a significance level established at p < 0.05. The analysis revealed a significant relationship between age and diabetic ulcer healing (p = 0.006). Patients aged 36–45 years were predominantly observed to achieve wound healing within 1–24 weeks. A significant association was also found between the duration of diabetes and ulcer healing (p = 0.000), with patients who had suffered from diabetes for less than 10 years showing better healing outcomes. In addition, adherence to a diabetic diet was significantly associated with ulcer recovery (p = 0.000). These findings suggest that demographic and clinical factors, particularly age, disease. duration, and dietary compliance, contribute to the healing process of diabetic ulcers. The study demonstrated that age, length of time living with diabetes, and adherence to dietary recommendations were significantly associated with diabetic ulcer healing in patients with Type 2 Diabetes.